Validity of hip‐worn inertial measurement unit compared to jump mat for jump height measurement in adolescents. (5th July 2018) - Rantalainen, Timo; Hesketh, Kylie D.; Rodda, Christine; Duckham, Rachel L.
Abstract : Jump tests assess lower body power production capacity, and can be used to evaluate athletic ability and development during growth. Wearable inertial measurement units (IMU) seem to offer a feasible alternative to laboratory‐based equipment for jump height assessments. Concurrent validity of these devices for jump height assessments has only been established in adults. Therefore, the purpose of this study was to evaluate the concurrent validity of IMU‐based jump height estimate compared to contact mat‐based jump height estimate in adolescents. Ninety‐five adolescents (10‐13 years‐of‐age; girls N = 41, height = 154 (SD 9) cm, weight = 44 (11) kg; boys N = 54, height = 156 (10) cm, weight = 46 (13) kg) completed 3 counter‐movement jumps for maximal jump height on a contact mat. Inertial recordings (accelerations, rotations) were concurrently recorded with a hip‐worn IMU (sampling at 256 Hz). Jump height was evaluated based on flight time. The mean IMU‐derived jump height was 27.1 (SD 3.8) cm, and the corresponding mean jump‐mat‐derived value was 21.5 (3.4) cm. While a significant 26% mean difference was observed between the methods (5.5 [95% limits of agreement 2.2 to 8.9] cm, P  = 0.006), the correspondence between methods was excellent (ICC = 0.89). The difference between methods was weakly positively associated with jump height ( r  = 0.28, P  = 0.007). Take‐off velocity‐derived jump height was also explored but produced only fair congruence. In conclusion, IMU‐derived jump height exhibited excellent congruence to contact mat‐based jump height and therefore presents a feasible alternative for jump height assessments in adolescents.